Exploring the Teaching Practice of ELT Pre-service Teachers to Develop Gender-responsive Pedagogy - Rida Cahyani Dwi Sukamto; Mirjam Anugerahwati; Evi Eliyanah (Universitas Hamzanwadi, 2024)
Integrating gender-inclusive strategies in teacher training prepares future educators to create fair and inclusive classrooms. Addressing gender biases in education can expand equal learning opportunities, positively impacting students' experiences and outcomes. This paper examines how Indonesian pre-service teachers implement gender-responsive pedagogy (GRP), focusing on their choices in teaching materials, classroom management, and instructional methods as they prepare to shape future learning environments. Four Indonesian ELT pre-service teachers from Universitas Negeri Malang participated in the study, closely examining them through classroom observations and semi-structured interviews. The thematic analysis of the interviews and observations revealed that pre-service teachers incorporated gender-responsive pedagogy (GRP) elements into their teaching practices, including diverse teaching materials, inclusive classroom management, and methods encouraging equitable student participation. These practices seemed to stem from the general inclusive teaching principles emphasized in their teacher education program. The findings indicate a potential benefit in integrating specific GRP training within professional education frameworks, enabling pre-service teachers to develop a deeper and more intentional understanding of gender-responsive strategies. This integration would empower future educators to address gender biases effectively and foster classrooms that actively support gender equality, enhancing students' educational experiences and outcomes.